Captopril + hydrochlorothiazide 24 h ambulatory monitoring effects - Asmar, R. G. (1987)
1 The purpose of this study was to evaluate over a 24 h period the antihypertensive effect of captopril 50 mg + hydrochlorothiazide (HCTZ) 25 mg once a day in mild to moderate hypertension. 2 Ambulatory recordings over 24 h of the blood pressure using the Spacelabs system were performed, at the end of a 15-day placebo period and after giving captopril + HCTZ for 45 days. 3 Captopril + HCTZ significantly decreased (P < 0.001) systolic and diastolic blood pressures for both the diurnal period (8 h to 22 h) and the nocturnal period (22 h to 8 h). No change in heart rate was observed. 4 For further analysis, the mean hour values of blood pressure and heart rate were calculated. A constant decrease of the systolic and diastolic blood pressure throughout the 24 h was obtained after captopril + HCTZ without any change in heart rate and in nyctohemeral variations. 5 The study provided evidence that, in patients with mild to moderate essential hypertension, captopril + HCTZ once a day decreased systolic and diastolic blood pressure all day long without any change in the heart rate and the blood pressure nyctohemeral cycle.